Clarifying the value relevance of voluntary carbon reporting: the case of Malaysian carbon-intensive industries. (27th January 2020) - Rahman, Noor Raida Abd; Rasid, Siti Zaleha Abdul; Basiruddin, Rohaida
This study aimed to empirically test the value relevance of voluntary carbon reporting (VCR) by Malaysian public listed companies operating in carbon-intensive industries from 2010 to 2016. Using panel data regression models, this study considered the impact of VCR from both, accounting and market-based perspectives. The quality of VCR is measured using the content analysis of disclosure indexes adapted from a list of disclosure items that were provided in various global warming, climate change, greenhouse gases, and carbon reporting guidelines, standards and frameworks. The finding indicated that on average, the quality of VCR was still low compared to the overall potential score. The findings also revealed that VCR generates a negative relationship with return on assets (ROA) and earnings per share (EPS). Nevertheless, VCRQ does not influence return on equity and Tobin's Q. This study has implications on both the policy and practice of organisations seeking to improve VCR practices.